Carbohydrate Antigen 125: A Biomarker at the Crossroads of Congestion and Inflammation in Heart Failure - Marko Kumric (Cardiac Failure Review, 2021)
Because heart failure (HF) is more lethal than some of the common malignancies in the general population, such as prostate cancer in men and breast cancer in women, there is a need for a cost-effective prognostic biomarker in HF beyond natriuretic peptides, especially concerning congestion, the most common reason for the hospitalisation of patients with worsening of HF. Furthermore, despite diuretics being the mainstay of treatment for volume overload in HF patients, no randomised trials have shown the mortality benefits of diuretics in HF patients, and appropriate diuretic titration strategies in this population are unclear. Recently, carbohydrate antigen (CA) 125, a well-established marker of ovarian cancer, emerged as both a prognostic indicator and a guide in tailoring decongestion therapy for patients with HF. Hence, in this review the authors present the molecular background regarding the role of CA125 in HF and address valuable clinical aspects regarding the relationship of CA125 with both prognosis and therapeutic management in HF.